Lessons Learned From Failures and Success Stories of HIV Breakthroughs: Are We Getting Closer to an HIV Cure? - Kalidasan, V.; Theva Das, Kumitaa (Frontiers in Microbiology, 2020)
There is a continuous search for an HIV cure as the success of ART in blocking HIV replication and the role of CD4+ T cells in HIV pathogenesis and immunity do not entirely eradicate HIV. The Berlin patient, who is virus-free, serves as the best model for a ‘sterilising cure’ and many experts are trying to mimic this approach in other patients. Although failures were reported among Boston and Essen patients, the setbacks have provided valuable lessons to strengthen cure strategies. Following the Berlin patient, two more patients known as London and Düsseldorf patients might be the second and third person to be cured of HIV. In all the cases, the patients underwent chemotherapy regimen due to malignancy and hematopoietic stem cell transplantation (HSCT) which required matching donors for CCR5Δ32 mutation - an approach that may not always be feasible. The emergence of newer technologies, such as long-acting slow-effective release ART (LASER ART) and CRISPR/Cas9 could potentially overcome the barriers due to HIV latency and persistency and eliminate the need for CCR5Δ32 mutation donor. Appreciating the failure and success stories learned from these HIV breakthroughs would provide some insight for future HIV eradication and cure strategies.